Analysis of English Language Ability of Food and Beverage Service Employees at Radisson Blu Bali Uluwatu Hotel - Goni, Glory Sharon Dian Janiellin; Tenda, Mirjam Pratidina; Lumare, Mercy A. (Journal of Psychology and Sustainable Education, 2025)
Good English language skills significantly affect guest satisfaction and hotel reputation. This study aims to analyze the English language skills of employees in the Food and Beverage Service Department of the Radisson Blu Bali Uluwatu Hotel. This study uses a qualitative method with a descriptive approach. Data collection through observation of employees in the Food and Beverage Service Department of the Radisson Blu Bali Uluwatu Hotel. The study results indicate that some employees have basic English language skills. However, some employees still need to improve their English language skills. This is due to obstacles in communicating effectively with foreign guests regarding grammar and vocabulary. The results of this study are expected to be a reference for hotel management to improve the quality of service and guest satisfaction by improving employees' English language skills.